Em nome da ordem: a Prefeitura Municipal de Natal como espaço da sub- versão - Leite, José Evangilmárison Lopes (2008)
The main goal of this work is analyze the way which the Natal City Prefecture was constructed as a place of subversion by those we call defenders of the order, in the period right after the outbreak of military coup in 1964. To reach it, the main resource of search was the Relatório Subversão no Rio Grande do Norte , document produced from the investigations realized in Natal City Prefecture as a result of the Commission of Inquiry s work, established by the governor Aluízio Alves to determine the subversion in Rio Grande do Norte s society. Based on the anti-comunist speech. That document introduces other image of the Prefecture, which activities developed by de second Djalma Maranhão administration (1961-1964), specially those developed in the educational area, as the campaign De Pé no Chão Também se Aprende a Ler , were considered subversive , communist , dangerous , threatening , names that served as backing to embed Natal City Prefecture in the general view about subversion existing in Rio Grande do Norte, according to the repression speech in this initial period of military regime. Key-words: 1964 Military Coup Natal City Prefecture